ANALYSIS OF THE EFFECTIVENESS FACTORS OF THE AUDIT QUALITY CONTROL SYSTEM AT THE BPK REPRESENTATIVE OFFICE OF NORTH SUMATERA PROVINCE - Muhammad Zamroni; Maya Sari (PT. Radja Intercontinental Publishing, 2026)
This study analyzes the factors that influence the effectiveness of the audit quality control system at the Audit Board of Indonesia (BPK) Representative Office in North Sumatra Province, where the quality control performance target has not been achieved in the past five years. The purpose of this study is to explain the influence of e-audit, tiered review, workload, and time pressure on the effectiveness of the system. The method used is qualitative with in-depth interviews and document analysis. The results indicate that the effectiveness of quality control is not optimal due to limited e-audit utilization, increasing workload and time pressure, and the implementation of reviews that are not substantive. However, the BPK has made improvements through the formation of a Review Support Team, audit quality checklist, cross-team reviews, and TPHP. This study expands the application of contingency theory in public sector audits and provides recommendations for the BPK to strengthen its technology-based quality system. The limitations of this study are its limited scope to one region and its descriptive nature that cannot be generalized.